Rencana Pengembangan Sumber Daya Manusia (SDM) Pendidik dan Tenaga Kependidikan Pondok Pesantren - Tulili, Ammalia; Dino; Asmendri; Sari, Milya (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2025)
The development of Human Resources (HR) in Islamic boarding schools (Pondok Pesantren) is a crucial aspect of improving the quality of education. As traditional Islamic educational institutions, pesantren play a strategic role in producing a generation that not only masters religious knowledge but also acquires skills relevant to modern demands. Strengthening educators' competencies enables pesantren to implement innovative and effective teaching methods. However, HR development faces challenges such as limited access to advanced training for educators, low perception of its importance, and the diverse backgrounds of the teaching staff. Nevertheless, HR development in pesantren also contributes to character building for students, where qualified educators serve as role models in morals and behavior. This study, conducted using a library research method, emphasizes the importance of systematic and sustainable HR development. The findings can guide pesantren administrators in designing training programs that are accessible and tailored to the unique needs of their educators. Furthermore, integrating HR development with character-building efforts is deemed essential for strengthening moral and ethical foundations. Through collaboration with governments and private institutions, pesantren can provide resources and training to ensure their sustainability while preserving traditional values and meeting the demands of modern education.